The Tao of Islam: Ceng Ho and the Legacy of Chinese Muslims in Pre-Modern Java - Sumanto Al Qurtuby (Studia Islamika, 2009)
The fact that "Sino-Javanese Muslim Cultures" are scattered over Banten, Jakarta, Cirebon, Semarang, Demak, Jepara, Lasem, Gresik, and Surabaya on the northern coast of Java (see also below) is strong evidence of the encounter between Cheng Ho (and other Chinese Muslims) and Javanese societies over the fourteenth and fifteenth centuries. These "Sino-Javanese Muslim cultures" are not only found in the form of mosques which show evidence of acculturation processes between China, Islam, and Java, but also in literature, arts, and other artifact Seen from another perspective, these historical facts illustrate the Chinese major role in spreading Islam in the region. Unfortunately, although the Chinese contribution in shaping Indonesian civilizations and Javanese cultures is apparent, only a few scholars have concerned themselves with the issue.DOI: 10.15408/sdi.v16i1.489